Pedunculated pulmonary artery intimal sarcoma with poor uptake in 18F-FDG PET/CT: A case report. Issue 3 (September 2021) - Takauchi, Takumi; Murai, Ryosuke; Musiake, Kazunori; Akaike, Yoko; Hirayama, Masaya; Ueda, Atsushi; Komiya, Tatsuhiko; Kadota, Kazushige
Abstract: Pulmonary artery intimal sarcoma (PAIS) is a rare tumor with an incidence of 0.001%–0.03% that usually grows along artery walls and absorbs fluorodeoxyglucose. It is difficult to distinguish PAIS from pulmonary thromboembolism due to the similarities of their symptoms. Therefore, contrast-enhanced computed tomography and positron emission tomography-computed tomography (PET-CT) should be used to establish a correct diagnosis. Here we report a case of an extremely rare type of PAIS, pedunculated PAIS, which could not be visualized on PET-CT. Histological features of a tumor with a low accumulation of fluorodeoxyglucose revealed low-cellularity and necrotizing background. Multimodal imaging was useful to diagnose PET-CT negative PAIS accurately. <Learning objective: Pedunculated pulmonary artery intimal sarcoma (PAIS) is a rare form of neoplasm. You need to know that PAIS which has low cellularity with marked interstitial myxoid tissue cannot be detected on positron emission tomography-computed tomography.>